SP10.1.5 Are we utilising the predictive potential of FIT during a time of resource scarcity?. (28th October 2021) - Carswell, Victoria; MacLeod, Campbell; Watson, Angus; MacKintosh, John; Docherty, James
Abstract: Aims: The COVID-19 pandemic has resulted in an unprecedented challenge. With the abolition of all non-urgent endoscopies nationwide, there has been concerning implications on colorectal cancer (CRC) diagnosis. Rationing of these scarce colonoscopy slots has become a priority. Faecal immunohistochemistry test (FIT) results are predictive of bowel pathology. Here we audit the clinical outcomes of patients that have undergone FIT in our health board in the pre and COVID-19 era. Methods: Using business intelligence methods, an automated system for NHS eHealth data collection has been established. All patients who have undergone FIT testing are audited for clinical outcomes including investigation and pathology. Results from December 2018-2019 (pre-COVID) were compared to December 2019-January 2021 (COVID). Results: There was a 70.12% increase in FIT uptake. 58.88% were female. Median age 73 (range 1-100). FIT results are compared below. Conclusion: Our business intelligence approach has improved uptake of FIT in our community. There have been proportionally higher rates of colorectal cancer diagnosis with less resources. FIT specificity is 98.64% and therefore should be further widely accepted to ration resources.